Architecture of a multi-service app module of on-demand transportation system - Zebda, Ahmed Yacine; Remmache, Mohamed Idris; Ben Saad, Mohamed Lahcen (Université Amar Telidji - Laghouat - Département d'informatique, 2020)
The demand for transportation is at an all time high and is continuing to increase with time and the availability of commercial vehicles is also increas- ing alongside it. We all know the importance that transportation holds in maintaining the flow of goods and cash as well as its role in the economy. The problem is that although transportation is available, people don't have easy access to it and more often than not they have to resort to traditional meth- ods to find suitable transportation.The ain of this work is to create a plat- forms that organizes the process of transportation and helps both drivers and possible clients to better interact and find work (drivers) and transportation (clients) easily. The result is a platform that lets clients post requests that the drivers bid on and the clients then can choose the best offers that suit them, thereby solving the problem mentioned above.